P65 Hypertension in pregnancy prevalence, risk factors and outcomes for women birthing in ireland. (3rd September 2019) - Corrigan, L; O'Farrell, A; Daly, D; Moran, P; Delaney, V
Abstract : Background: Hypertensive disorders of pregnancy account for nearly 18% of all maternal deaths world-wide. They are associated with increased risk of maternal and neonatal morbidity, adverse pregnancy outcomes and long-term health risks for both mother and baby. This study aims to determine prevalence, risk factors and outcomes associated with hypertensive disorders of pregnancy (Pregnancy-induced hypertension, pre-eclampsia, eclampsia, HELLP, hypertensive disorder of pregnancy unspecified). Methods: Data on maternity hospital discharges (ICD codes O00-O99) for women giving birth in Ireland in 2016 were extracted from Hospital In-Patient Enquiry (HIPE) using Health Atlas. Women discharged following delivery were identified using ICD-10 codes O80-O84 for delivery. Those with a diagnosis of a hypertensive disorder of pregnancy were identified using ICD-10 codes O10-O16. Frequencies and descriptive statistics were used to present prevalence rates of hypertensive disorders of pregnancy. Pearson's Chi-square and multivariate analyses were conducted to identify risk factors. Data was analysed in SPSS version 25 and JMP version 9. Results: Of 60, 188 births, 3531 women (5.9%) had a hypertensive disorder of pregnancy. Rates were higher among women with pre-existing diabetes, gestational diabetes, obesity and those age ≥40years (p<0.001). Women with a diagnosis of a hypertensive disorder of pregnancy had a higher risk of poor foetal growth (OR 2.6), preterm labour and birth (OR 3.7), placental abruption (OR 2.0), long labour (OR 1.4), instrument–assisted delivery (OR 1.2), caesarean section (OR 1.8), postpartum haemorrhage (OR 1.6) and length of stay ≥6 days (OR 5.6). After adjusting for all factors, obesity (OR 4.3) pre-existing diabetes (OR 3.5), gestational diabetes (OR 1.5) and being aged ≥ 40 years (1.5) remained significantly associated with being diagnosed with a hypertensive disorder. Conclusion: As the number of overweight and obese pregnant women, women giving birth aged ≥ 40 years, and those with pre-existing diabetes mellitus or new onset gestational diabetes increase rates of hypertensive disorders of pregnancy will likely become more common obstetric risks. They therefore represent a significant public health concern. These findings can help inform strategies for identifying factors associated with hypertensive disorders of pregnancy.